Tracing Cr, Pb, Fe and Mn ocurrence in the Bahia Blanca estuary through commercial fish species - la Colla, Noelia Soledad (2017)
Over the last decades the anthropogenic contamination impact has substantially increased in the Bahía Blanca estuarine area, and scarceinformation exists regarding metals in the biotic compartment of this estuary. Thus, fish tissues were used to evaluate metal accumulation within this aquatic environment. The study focused on the determination of Cr, Pb, Fe and Mn in the gills, liver and muscle tissues of six commercial fish species (Brevoortia aurea, Odontesthes argentinensis, Micropogonias furnieri, Cynoscion guatucupa, Mustelus schmitti and Paralichthys orbignyanus).From the results it can be summarized that C. guatucupa tends to accumulate higher metal levels in the liver tissues, mostly Cr and Fe, than the other studied species. O. argentinensis and P. orbignyanus, both permanent34 inhabitants of the BBE, achieved the highest metal values in the gill tissues, mostly in comparison to M. schmitti. The gill tissues were found to be the main organ of Mn and Ni accumulation for most species, whereas in general, minimum concentrations were found for all the analyzed metals in the muscle tissues. Nevertheless, and according to the guidelines, all fish species showed  at least one sample with concentrations of Mn and/or Cr above the permissible levels for human consumption. Finally, it was highlighted the usefulness of selecting these fish species as bioindicators of metal pollution, since they are either permanent inhabitants of the estuary or, according to the sizes under analyses, spend much of their time in this coastal waters.